Collaborative Governance in Tourism Village Development in Ciamis Regency, West Java Province, Indonesia - Nurwanda, Asep; Daraba, Dahyar; Suprajogo, Tjahjo; Puspita, Diah (International Journal of Science and Society, 2024)
Tourism villages are a potential sector in the development of an area with very minimal risk of environmental damage. This makes village tourism a leading sector for all villages, including villages in Ciamis Regency. The development of tourist villages in the normative and empirical process needs to be carried out through collaborative governance because tourist villages have multidimensional characteristics. The development of tourist villages in Ciamis Regency is still not optimal because even though it has great potential and is supported by the Tourism Information Center, it turns out that the development process is still carried out separately between all parties involved. The aim of this research is to analyze collaborative government governance in developing tourist villages and find an ideal collaborative governance model in developing tourist villages in Ciamis Regency. For this purpose, Ansell and Gash's government collaboration theory is used which includes four dimensions, namely initial conditions, facilitative leadership, institutional design, and collaboration processes. The research uses a qualitative approach with descriptive research type. Data analysis was carried out through data reduction and drawing conclusions. The research results show that the ongoing tourism village development process has not fully adopted collaborative governance. This is because trust has not been formed in each of the actors involved. The ideal tourism village development model that adopts collaborative governance is the Tourism Development Model. This model prioritizes building trust and sustainable commitment to each actor in tourism village development.